Pemakaian Kontrasepsi Suntik DMPA dan Kejadian Amenorea Sekunder di Wilayah Kerja Puskesmas Lepo-Lepo Kota Kendari - Yustiari Yustiari (Politeknik Kesehatan Kemenkes Mamuju, 2019)
Injection hormonal contraception Depo-Medroxyprogesterone Acetat (DMPA) is a contraceptive method that is widely used in contraceptive services. This contraception has good effectiveness, and has a systemic way of working in the body, causing systemic side effects on the body. Injectable hormonal contraception consists of Norethindrone Enanthate (Net-En), Depo-Medroxy-Progesterone Acetate (DMPA) and Cyclofem. Side effects that can be caused include menstrual cycle disorders, tenderness in the breast, abdominal fullness, weight changes, dizziness and depression. Most DMPAusers will experience menstrual cycle disorders and are most disturbing. The effect of injecting contraception on amenorrhea increases with the length of time of use. Women have menstrual cycles that are not the same as each other. This can be influenced by various factors including the hormone estrogen, stress level, nutritional intake and heredity and disease. The aim of this study was to determine the association of DPMA injection contraceptive use with the incidence of secondary amenorrhea in the working area of ​​the Lepo-Lepo Health Center in Kendari City.The research design used was observational with a cross sectional study design. This research has been carried out at the Lepo-lepo Health Center. The sample in the study was EFA using injection contraception at the Lepo-Lepo Health Center in Kendari City, which amounted to 92 EFA. The instrument of data collection is a questionnaire. Data were analyzed by Logistic Regression test.The results showed that most acceptors had used DMPA injection contraception for ≥ 24 months (42.4%). Most DMPA injection KB acceptors experience secondary amenorrhea (66.3%). There was a significant relationship between the duration of DMPA injection contraception and the incidence of secondary amenorrhea.